The Influence of Individual, Job, and Organizational Characteristics on Organization Citizen Behavior (OCB) on Land Transportation Management Center Employees Region XV South Kalimantan - Ariani, Gusti Meinar Girda; Herawati, Ana Sofia; Mardah, Siti; Nurhayati, Netty (CV ODIS, 2023)
This study aims to determine and analyze whether there is an influence of Individual Characteristics, Work Characteristics and Organizational Characteristics on Organizational Citizen Behaviour at Balai Pegelola Transportasi Darat Wilayah XV Provinsi Kalimantan Selatan. This research is categorized as quantitative research with a questionnaire instrument. The population in this research is all employees of Balai Pegelola Transportasi Darat Wilayah XV Provinsi Kalimantan Selatan counted 135 people. Sampling technique by means of saturated sampling technique or census. The data used in this study is the primary data obtained through a questionnaire. The analysis method by using a validity test and reliability test using Cronbach Alpha. Measurers proved to be valid and reliable for research instruments. Multiple regression analysis is used to test the hypothesis of this research. Based on the results of this study it is known that the results of multiple linear regression test is Y = 0,951 + 0,195 X1 + 0,350 X2 + 0,387 X3 where, Individual Characteristic (X1), Work Characteristic (X2), Organization Characteristic (X3) and Organization Citizen Behaviour (Y). Then T test results of Individual Characteristics significantly affect of OCB (2,446 > 1,656). Work Characteristic has a significant effect that is (2,690 > 1,656) and Organization Characteristic (4,507 > 1,656) also has a significant effect. Test F together there is a significant influence on Organization Citizen Behaviour (247,626 > 3,06). R square test results give a value of 0,925 which means 92,5% employee satisfaction variable can be explained through two independent variables, while the rest of the 7,5% influenced or explained by other factors not included in this study.